Elucidation of serum levels of IL-17, IL-23 and their receptors in systemic lupus erythematosus patients : associations with serological parameter and disease activity - Aziz, Farah Izati (2020)
Interleukins (ILs) are a group of cytokines, mainly synthesised by CD4+ T helper cells, as well as by endothelial cells, monocytes and macrophages. ILs bind to their interleukin receptors and this is one of the pivotal factors in the development and progression of systemic lupus erythematosus (SLE). This study aimed to determine the serum levels of IL-17, IL-23 and their receptors; IL-17RA and IL-23R, in SLE patients compared with healthy controls. In addition, the associations of these interleukins and their receptors were associated with serological parameters and disease activity, specifically SLEDAI-2K score. SLE patients and healthy controls (n=50 in each group) were recruited in this study. The serum levels of IL-17 and IL- 23 were evaluated using pre-coated specific antibody via Human IL-17/IL-23 ELISA test. PBMCs were isolated from the peripheral blood using Histopaque-1077 density centrifugation and stained with fluorochrome-labelled antibodies for staining of surface IL-17RA and IL-23R, and their levels determined by flow cytometry analysis. SLE patients showed significantly elevated levels of IL-17RA and IL-23R (p<0.001) compared with healthy controls. Significant downregulation of serum IL- 17 (p<0.001) while no significant difference (p=0.73) in IL-23 levels were observed in SLE patients compared with healthy controls. In addition, no significant associations between IL levels with SLEDAI-2K and serological parameters. Interestingly, IL-17RA levels were significantly associated with antinuclear antibodies (ANA) (p=0.024) and IL-23R levels were significantly associated with higher SLEDAI-2K scores (p=0.011). However, the decreasing level of serum IL-17 might need further work as the relation with its receptor where the elevated IL-17RA expression is expected to take up most of the circulating serum IL-17 resulting in its reduced levels. In conclusion, we suggest that therapeutic inhibition of IL-17RA and IL-23R represents a potential treatment option for SLE patients.